2014
DOI: 10.1016/j.acra.2013.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative MRI Improves Prediction of Extensive Occult Axillary Lymph Node Metastases in Breast Cancer Patients with a Positive Sentinel Lymph Node Biopsy

Abstract: Rationale and Objectives To test the ability of quantitative measures from preoperative Dynamic Contrast Enhanced MRI (DCE-MRI) to predict, independently and/or with the Katz pathologic nomogram, which breast cancer patients with a positive sentinel lymph node biopsy will have ≥ 4 positive axillary lymph nodes upon completion axillary dissection. Methods and Materials A retrospective review was conducted to identify clinically node-negative invasive breast cancer patients who underwent preoperative DCE-MRI, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…For example, the decision to proceed with neoadjuvant chemotherapy is necessarily a judgment based on clinical stage without knowledge of pathologic stage and, thus, is based primarily on imaging, with MRI often playing a key role. It has been demonstrated that breast MRI is an accurate method for predicting extent of breast cancer as well as demonstrating axillary lymph node involvement through direct evaluation of the axilla . However, MRI may overestimate tumor size and underestimate axillary lymph node involvement; therefore, imaging has not yet obviated the need for surgical staging, including sentinel biopsy or axillary lymph node dissection …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the decision to proceed with neoadjuvant chemotherapy is necessarily a judgment based on clinical stage without knowledge of pathologic stage and, thus, is based primarily on imaging, with MRI often playing a key role. It has been demonstrated that breast MRI is an accurate method for predicting extent of breast cancer as well as demonstrating axillary lymph node involvement through direct evaluation of the axilla . However, MRI may overestimate tumor size and underestimate axillary lymph node involvement; therefore, imaging has not yet obviated the need for surgical staging, including sentinel biopsy or axillary lymph node dissection …”
Section: Introductionmentioning
confidence: 99%
“…Current research indicates that quantitative MRI tumor biomarkers, ie, phenotypes, rather than anatomic evaluation, may hold promise in predicting malignancy, breast cancer subtypes, molecular pathways, gene expression, and lymph node status . However, not enough literature is available to demonstrate whether computer‐extracted MRI phenotypes can augment the prediction of pathologic stage.…”
Section: Introductionmentioning
confidence: 99%
“…Though MRI is not recommended as a preoperative axillary evaluation method according to guidelines such as NCCN 2017 [4], integrating the information already gathered with regard to primary lesions and occult axillary lymph node risk will come at minimal additional cost. The capacity of breast MRI to predict additional axillary lymph node status is highly relevant for care of patients with SN+ findings [15]. Although AUS has been reported to have a similar specificity but better sensitivity than MRI [14], AUS is a subjective examination and it has some problems.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, tumor morphology, density and enhancement characteristics, as determined on MRI, have been shown as significant in differentiating breast cancers subtypes [16,17]. Similarly, prior investigations have associated certain breast tumor features to axillary nodal status using dynamic contrast-enhanced (DCE) MRI [18,19]. However, little is known about the role of the fat environment in predicting such adverse pathologic factors.…”
Section: Introductionmentioning
confidence: 96%